Effect of transfer time, temperature, and size on burrowing capacity of juvenile clams, Mulinia edulis, from hatchery. Issue 4 (23rd September 2018) - Abarca, Alejandro; Oliva, Doris; Toledo, Pedro
Abstract : Studies under laboratory and field conditions have shown that juvenile Mulinia edulis clams measuring 5–15 mm are able to tolerate transfer times of over 24 hr and burrow successfully. Burrowing generally followed an asymptotic curve over time, with a rapid initial phase for smaller juveniles, which slowed over time. In laboratory conditions, at low temperatures (8°C), juvenile burrowing was initially rapid (50–70% at first 2 min). In summer temperatures (15.5°C), the burrowing capacity of three sizes of juvenile clams was tested. Size determines differences in burrowing dynamics, where juveniles of 8.9 mm shell length (SL) take longer to burrow than smaller juveniles (4.9 and 6.3 mm SL). For longer transfer times in laboratory conditions (>12 hr), burrowing was slower. The results indicate a faster burrowing rate in smaller (<10 mm) juvenile clams than in larger ones. Transfer times over 24 hr in field experiments show burrowing levels of over 50% after a 60‐min evaluation, with larger juveniles (>10 mm) requiring longer for burrowing. Based on our results, we suggest sending seeds out to grow in natural environments at SL <10 mm, temperatures below 12°C, and transfer times shorter than 12 hr. These results are valuable for improving future transfer techniques from hatchery to growout for small‐scale aquaculture of this new native species in South America.